Digital Core Tax Literacy in Milkfish MSMEs - Made Dudy Satyawan; Aisyaturrahmi; Lintang Venusita (PT Inovasi Pratama Internasional, 2026)
The implementation of Core Tax, which officially came into effect in Indonesia in January 2025, is part of the tax reform to create a modern, integrated, and digital-based tax administration system. However, the implementation of this system still faces various challenges, especially for Micro, Small, and Medium Enterprises (MSMEs) that have limited digital literacy and tax understanding. This community service activity aims to improve digital tax literacy and tax compliance of MSMEs in the milkfish processing industry center in Gresik Regency, with UD Multi Sarana Niaga (“Bandeng Mentari”) as a partner. The implementation method includes identifying partner needs, socializing the latest tax regulations, assisting in the use of the Core Tax application, and developing a practical guide module for managing Core Tax for MSMEs. The results of the activity indicate an increase in partner understanding of tax regulations, operational capabilities in using the Core Tax system, and the alignment between commercial and fiscal financial reporting. In addition, this activity raises awareness among MSMEs regarding the role of tax in national development and business sustainability. This program is also strengthened through international dissemination with Rajamangala University of Technology Krungthep (Thailand) which is aligned with Sustainable Development Goals (SDGs) point 9 on industry, innovation, and infrastructure.